What Is Your mPINC Score?. Issue 4 (July 2016) - Spatz, Diane L.
Abstract : Do you know your hospital's mPINC (Maternity Practices in Infant Nutrition and Care) score? You should. Our breastfeeding expert, Dr. Spatz, explains this important metric of breastfeeding practices in the hospital setting.